2020
DOI: 10.3390/catal10020165
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured Equimolar Ceria-Praseodymia for Total Oxidations in Low-O2 Conditions

Abstract: A Gasoline Particulate Filter (GPF) can be an effective solution to abate the particulate matter produced in modern direct injection gasoline engines. The regeneration of this system is critical, since it occurs in oxygen deficiency, but it can be promoted by placing an appropriate catalyst on the filter walls. In this paper, a nanostructured equimolar ceria-praseodymia catalyst, obtained via hydrothermal synthesis, was characterized with complementary techniques (XRD, N2-physisorption, FESEM, XPS, Temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 59 publications
2
10
0
Order By: Relevance
“…Upon introduction of small amounts of a second lanthanide, the cube-shaped crystal is usually maintained, but it has been reported that at higher substituent levels, and under otherwise identical reaction conditions, the crystal morphology becomes increasingly rod-shaped, with a distribution of both crystal forms at intermediate compositions. This is exemplified by the case of praseodymium, where the same phenomenon has been reported independently by several different research groups: [105][106][107][108] at 25% Pr substitution and above, the rod-like crystal morphology is detected, and an example is shown in Figure 13. Praseodymium may also be found in the +4 oxidation state, and this has been inferred from the redox properties of some of these samples [106,108] and detected by X-ray spectroscopy in others [105,107].…”
Section: Rare Earth-substituted Ceriasupporting
confidence: 71%
See 1 more Smart Citation
“…Upon introduction of small amounts of a second lanthanide, the cube-shaped crystal is usually maintained, but it has been reported that at higher substituent levels, and under otherwise identical reaction conditions, the crystal morphology becomes increasingly rod-shaped, with a distribution of both crystal forms at intermediate compositions. This is exemplified by the case of praseodymium, where the same phenomenon has been reported independently by several different research groups: [105][106][107][108] at 25% Pr substitution and above, the rod-like crystal morphology is detected, and an example is shown in Figure 13. Praseodymium may also be found in the +4 oxidation state, and this has been inferred from the redox properties of some of these samples [106,108] and detected by X-ray spectroscopy in others [105,107].…”
Section: Rare Earth-substituted Ceriasupporting
confidence: 71%
“…Applications of rare earth-substituted ceria materials span the types of fields expected for these materials, from oxide ion conductors in solid oxide fuel cells, where the enhanced sinterability of fine powders into ceramics is beneficial [136,137,143,149,150], to catalysts for CO and soot oxidation, where the high surface and exposure of specific crystal faces may offer some benefits [103,105,107,108,113,115,132,133,135,[150][151][152][153]. Photocatalytic properties are of increasing focus for degradation of pollutants or organic transformations, and some of the rare earth-substituted materials have been screened for these applications [101,124,141,154].…”
Section: Rare Earth-substituted Ceriamentioning
confidence: 99%
“…In the last years, a lot of research has been conducted for GPFs to optimize their efficiency and performance. Topics included filter structure [10], flow field [11], filter material [12], in particular for soot oxidation at absence of NO x and O 2 [13,14], soot storage and oxidation [15,16], oxygen storage [17], ash loading [18], and washcoat [19]. Typically, the temperature at the GPFs is high enough to oxidize the soot when there is available oxygen (e.g., during fuel cut-offs) [20].…”
Section: Introductionmentioning
confidence: 99%
“…This Special Issue includes three reviews [1][2][3] and three articles [4][5][6]. The review by Lisi et al [1] addresses the most important issue to an effective regeneration of catalytic (i.e., catalyst-coated) diesel particulate filters (DPFs): the contact between soot and catalyst.…”
mentioning
confidence: 99%
“…In this framework, Aneggi and Trovarelli [5] compared the behavior of ceria-zirconia and zirconia in soot oxidation under oxygen-poor conditions, showing that lattice and surface oxygen in the former can help with oxidation at low oxygen partial pressure. Sartoretti et al [6] investigated a nanostructured equimolar ceria-praseodymia catalyst for different reactions, namely CO oxidation, ethylene and propylene total oxidation, and soot combustion, in low oxygen availability. They found that, thanks to its capability of releasing active oxygen species, this catalyst exhibited a remarkable activity and CO 2 selectivity at low oxygen concentrations.…”
mentioning
confidence: 99%